IInterpretasi Dan Makna Kritik Sosial Dalam “Komik Strip Untuk Umum (Kostum)” Periode 1 Desember – 31 Desember 2017 - Salam, Babus; Prasetyo, Iwan Joko; Susilo, Daniel (LONTAR: Jurnal Ilmu Komunikasi, 2018)
Theres many ways can be done to appreciate the voices of messages and criticisms through creative ways, one of them through comics. One of the Indonesian comic artists who used comics as a medium of social criticism was Haryadhi through his "Komik Strip Untuk Umum (KOSTUM)” creation. KOSTUM Comics record the events that are happening and pour them into comic strips spread through social media. This research is a qualitative descriptive type using Roland Barthes' semiotics theory with two-stage significance (two orders of signification). From the results of the study, researchers found the implicit meaning that is to criticize and satirize the behavior of Indonesian people in a subtle way. Criticism expressed to comics is directed directly at the actors but is delicately wrapped with humorous portrayals through their characters. From the KOSTUM comics examined can be concluded that the social criticism described in the comic is an expression of the condition of the community related to the values that are used as a guideline for living in community groups.Keywords: Comics, Social Criticism, Semiotics, Roland Barthes